Corporate Finance Practices: The Perspective of Qatar Firms - Haider, Shahrazad Sabri (2014)
The purpose of this research was to examine the perceptions of the CFOs of private and listed firms in Qatar on current corporate finance practices and decision making namely, cost of capital, capital budgeting, capital structure, and dividend policy. The research specifically examines the survey responses of CFOs according to CFO’s characteristics and firm’s attributes such as CFO’s education, tenure, age, firm size, sector, equity, and target debt ratio. Using descriptive and exploratory research design and using purpose sampling method, a primary questionnaire survey with 100 CFOs, who are working in both public and private firms in Qatar,was conducted. The questionnaire survey was designed with 18 closed-ended structured questions (multiple choice and multiple response questions) to collect data regarding the questions in the area that are closely related to corporate finance practices, capital budgeting,cost of capital, dividend policy and capital structure. The results of this research indicated the application of basic corporate finance tools that are coherent with what is taught in the classrooms. As such the results revealed that firms are widely using IRR today as capital budgeting technique for decision making despite its limitation observed. Also, it is reported that CAPM is no popular among firms for estimating the Cost of equity capital while WACC has emerged as the most preferred method due to the simplicity of tax system in Qatar. The results of this research manifested the Bird-In-Hand dividend theory. The results indicated that firms in Qatar do not have particular source of capital structure choices when making decisions of how to best finance their projects as in the case of the US market. The findings of this research indicated that finance theory is not yet fully implemented in Qatar. The results also showed evidence that corporate finance practices vary depending on management and firm characteristics.